Macroeconomic variables analysis towards foreign direct investment in developing countries / Sherly Jackson - Jackson, Sherly (2017)
The link between macroeconomic variables and Foreign Direct Investment (FDI) flows has been investigate by several empirical studies. This study investigate the macroeconomic variables which is exchange rate, gross domestic product, inflation and current account analysis towards foreign direct investment in developing countries. Panel data 15 countries in developing countries base on the International Monetary Fund (IMF) and 10 years in range from 2006 until 2015 were used to investigate the relationship and the impact between macroeconomic variables and foreign direct investment. The data has been run using Stata 12 Version for the overall result and eView 9 for test the panel unit root test (LLC). This study using the Breusch Pagan Lagrangian Multpilier Test (BPLM) and Hausman Test to investigate the relationship and impact between the macroeconomic variables towards the foreign direct investment.